PENERAPAN SISTEM PRESENSI DAN PENGGAJIAN KARYAWAN MENGGUNAKAN BARCODE BERBASIS ONLINE DENGAN METODE RAPID APPLICATION DEVELOPMENT PADA CP. FRANSISCO MAHARANI JNT EXPRESS TANGERANG - Ravafy, Van (PT Triputra Sejahtera Prima, 2024)
In the current technological era, CP. Francisco Maharani JNT Express Tangerang, an expedition company, still uses a manual attendance and payroll system which is prone to errors and takes a long time. This research aims to build an online-based employee attendance and payroll system using barcodes using the Rapid Application Development (RAD) method. The RAD method is used to speed up the system development process by directly involving users in each development stage. This system was built using the PHP programming language and MySQL database. The research results show that an online-based employee attendance and payroll system using barcodes can increase the efficiency and accuracy of employee attendance and payroll data. This system can also save company time and costs. Keywords: Presence Information System, Payroll, Barcode, RAD xi+104 pages; 46 figures; 19 tables; 3attachments Bibliography: 51 (2019-2023)